After the halcyon days: the anti-/alterglobalization movement and international organizations, 1996–2011. Issue 1 (2nd January 2016) - Fogarty, Edward A.
ABSTRACT: Why are relations between non-governmental organizations (NGOs) and international organizations (IOs) sometimes conflictual and other times collaborative? This article evaluates hypotheses in the international relations and social movements literatures with reference to relations between NGOs associated with the anti-/alterglobalization movement and multilateral economic institutions (MEIs). Drawing on an original database and interviews with MEI and NGO staff members, the article shows that attributes of NGOs – including NGO budgets, ideology, and organizational structure – rather than the political or economic environment better account not only for an overall increase in collaboration with IOs since the late 1990s, but also for a growing divergence among NGOs regarding the acceptability of such collaboration.